EFFECT OF GnRH DURING VARIOUS STAGES OF ESTRUS CYCLE ON FERTILITY AND PLASMA PROGESTERONE IN BUFFALOES - MANDAL, D D; SRIVASTAVA, S K; KUMAR, P (The Indian Journal of Animal Reproduction, 2023)
This study was aimed to see the effect of GnRH administration on progesterone profile andconception in buffaloes. Forty parous buffaloes were divided into five groups each of eight animals.Animals in group I, II and Ill were administered GnRH (2.5 ml. Receptal) on day-0, day-5 and day-12 ofestrus cycle, respectively, whereas group IV animals received same dose of GnRH on all three days,ie day-0, 5 and 12 of cycle. Group V received normal saline on the same days as above and served ascontrol. Progesterone concentration was significantly higher (P
Keywords: Buffaloes; GnRH; Progesterone; Fertility